Identification of a Small Compound Targeting PKM2-Regulated Signaling Using 2D Gel Electrophoresis-Based Proteome-wide CETSA. Issue 2 (20th February 2020) - Nagasawa, Ikuko; Muroi, Makoto; Kawatani, Makoto; Ohishi, Tomokazu; Ohba, Shun-ichi; Kawada, Manabu; Osada, Hiroyuki
Summary: The cellular thermal shift assay (CETSA) has recently been devised as a label-free method for target validation of small compounds and monitoring the thermal stabilization or destabilization of proteins due to binding with the compound. Herein, we developed a modified method by combining the CETSA and proteomics analysis based on 2D gel electrophoresis, namely 2DE-CETSA, to identify the thermal stability-shifted proteins by binding with a new compound. We applied the 2DE-CETSA for analysis of a target-unknown compound, NPD10084, which exerts anti-proliferative activity against colorectal cancer cells in vitro and in vivo, and identified pyruvate kinase muscle isoform 2 (PKM2) as a candidate target protein. Interestingly, NPD10084 interrupted protein-protein interactions between PKM2 and β-catenin or STAT3, with subsequent suppression of downstream signaling. We thus demonstrate that our 2DE-CETSA method is applicable for identification of target compounds discovered by phenotypic screening. Graphical Abstract: Highlights: 2D gel electrophoresis-based proteome-wide CETSA, namely 2DE-CETSA, was developed Cell-based screening identified NPD10084 as an anti-cancer compound Analysis by 2DE-CETSA revealed thermal destabilization of PKM2 by NPD10084 NPD10084 suppressed non-glycolytic PKM2-regulated signaling in cancer cells Abstract : Nagasawa et al. developed a proteome-wide cellular thermal shift assay (CETSA) method "2DE-CETSA" to identify thermal stability-shifted proteins due to interactions with a small compound. Using 2DE-CETSA, they have shown that an anti-cancer compound NPD10084 induced thermal destabilization of PKM2. NPD10084 disrupted the PKM2 complex and inhibited downstream signaling.